Human cytomegalovirus UL29/28 protein interacts with components of the NuRD complex which promote accumulation of immediate-early RNA. - Scott S Terhune; Nathaniel J Moorman; Ileana M Cristea; John Paul Savaryn; Christian Cuevas-Bennett; Michael P Rout; Brian T Chait; Thomas Shenk (PLoS Pathogens)
Histone deacetylation plays a pivotal role in regulating human cytomegalovirus gene expression. In this report, we have identified candidate HDAC1-interacting proteins in the context of infection by using a method for rapid immunoisolation of an epitope-tagged protein coupled with mass spectrometry. Putative interactors included multiple human cytomegalovirus-coded proteins. In particular, the interaction of pUL38 and pUL29/28 with HDAC1 was confirmed by reciprocal immunoprecipitations. HDAC1 is present in numerous protein complexes, including the HDAC1-containing nucleosome remodeling and deacetylase protein complex, NuRD. pUL38 and pUL29/28 associated with the MTA2 component of NuRD, and shRNA-mediated knockdown of the RBBP4 and CHD4 constituents of NuRD inhibited HCMV immediate-early RNA and viral DNA accumulation; together this argues that multiple components of the NuRD complex are needed for efficient HCMV replication. Consistent with a positive acting role for the NuRD elements during viral replication, the growth of pUL29/28- or pUL38-deficient viruses could not be rescued by treating infected cells with the deacetylase inhibitor, trichostatin A. Transient expression of pUL29/28 enhanced activity of the HCMV major immediate-early promoter in a reporter assay, regardless of pUL38 expression. Importantly, induction of the major immediate-early reporter activity by pUL29/28 required functional NuRD components, consistent with the inhibition of immediate-early RNA accumulation within infected cells after knockdown of RBBP4 and CHD4. We propose that pUL29/28 modifies the NuRD complex to stimulate the accumulation of immediate-early RNAs.